Bioactive Calcium Silico-Phosphate Glasses Doped with Mg2+ and/or Zn2+: Biocompatibility, Bioactivity and Antibacterial Activity - Laura-Nicoleta Dragomir; Cristina-Daniela Ghiţulică; Andreia Cucuruz; Andreea Lazar; Georgeta Voicu; Sorina Dinescu (Antibiotics)
Bioactive glasses in the SiO2-CaO-P2O5 system represent emerging materials for hard-tissue-regeneration applications. This article focuses on the synthesis, characterization, and biological interaction of glasses doped with Mg2+ and/or Zn2+, with an emphasis on their effects on biomineralization, antibacterial behavior, and interactions with preosteoblasts from the MC3T3-E1 cell line. The bioglasses were synthesized using the sol-gel method, and the vitreous nature remained predominant even after thermal treatment at 600 °C for 2 h. From an in vitro perspective, the synthesized bioglasses demonstrated strong cell adhesion and proliferation (notably in the case of Mg2+ doping), low cytotoxicity, and antibacterial properties (especially in Zn2+-doped samples). Additionally, the simultaneous doping with Mg2+ and Zn2+ of the bioactive glass matrix is a prospective strategy for developing biomaterials with a “dual” biological characteristics–both osteoinductive and antibacterial.